Against Liberal Muslims: Re-reading Boarding Schools’ Sanad-ijazah and Kyai-santri Through Gadamer and Lakatos’ Lens - Muhammad Daffa Syafiq Nashr ad-Diba'i (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2026)
This study critically analyzes the necessity of having a teacher within the Indonesian Islamic boarding school (pesantren) tradition through the lens of classical Islamic epistemology and contemporary philosophy of science. Employing qualitative hermeneutic-analytical approach based on library research adn focus group discussion, this investigation examines the epistemological validity of the teacher-student transmission system that has become the target of criticism from modern liberal Muslims such as Guru Gembul. The theoretical framework combines Hans-Georg Gadamer's philosophical hermeneutics (fusion of horizons) with Imre Lakatos's methodology of scientific research programmes to evaluate the pesantren tradition. Key findings reveal that: (1) the Arab-Islamic oral tradition practiced in pesantren is a sophisticated quality control system that anticipated insights of modern hermeneutics; (2) the sanad-ijazah system instantiates Gadamerian fusion of horizons where knowledge transmission is a dialogical encounter between tradition and context; (3) within Lakatos's, the pesantren tradition demonstrates characteristics of a progressive research programme over centuries, while liberal Muslim critiques exhibit mixed-evaluation; (4) critiques of "intellectual dependence" on teachers reveal a category mistake assuming epistemological autonomy ex-nihilo. This research contributes to contemporary Islamic epistemology discourse by demonstrating the necessity for epistemological justice that acknowledges the complexity of Islamic scholarly traditions often subordinated in modern discourse.